Struktur Komunitas Mangrove di Kelurahan Setapuk Besar Kota Singkawang - Mega Sri Astuti; Warsidah Warsidah; Ikha Safitri (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
Mangrove are plants that can survive in extreme areas with high salinity levels and have an important role for marine organisms. Mangrove are also a parameters that can absorb carbon much higher than other forest types. The purpose of this research was to observe mangrove community structures. This research was conducted from February to March 2020 in the mangrove ecosystem of Setapuk Besar Village. This research was conducted using purposive sampling method which is based on different environmental hues. The results showed that there were 4 types, namely Avicennia marina, Avicennia lanata, Rhizopora stylosa and Rhizopora mucronata. Species of A. marina at tree level have a density value of 66.55 Ind / ha and an Importance Value Index of 300%. Type A. marina at seedling level has a density value of 6266.66 Ind / Ha and an Importance Value Index of 200%. Seedling rate: The highest Importance Value Index for R. stylosa was 127.53%